Identifikasi Kebutuhan Psikoedukasi untuk Menurunkan Distres Psikologis pada Wanita dengan Kanker Payudara Pasca Mastektomi - Ningsih, Dewi Mustika; Prajoko, Yan Wisnu; Setyowibowo, Hari; Anggorowati, Anggorowati (Universitas Faletehan, 2023)
Women with breast cancer who underwent mastectomy treatment procedures got psychological problems as the impacts on thoughts, emotions, behaviors and physical sensations. They are categorized as psychological distress which requires psychoeducational needs identification. This research aimed to identify the need for psychoeducation to reduce psychological distress in post-mastectomy breast cancer women. This research was an exploratory, descriptive qualitative study with a thematic analysis approach using Atlas-ti7 software. The target population of the study was women with post-mastectomy breast cancer as inpatients. The sampling technique used was purposive sampling. A total of 15 participants underwent interviews. This research found five themes as issues (psychological concerns), namely problems with physical sensations, the impact of thoughts, the impact of emotions, lack of information and psychological support. 5 psychoeducational needs were identified, namely management strategies for overcoming physical problems, overcoming problems of negative thought effects, managing negative emotions, explaining information regarding the benefits and impacts of mastectomy, and how to ask for help to get psychological support. This research recommended five ways or techniques of fulfilling psychoeducational needs to reduce psychological distress, namely explaining the benefits and impacts of mastectomy, early ambulation and range of motion (ROM) techniques, deep breathing techniques, muscle progressive relaxation techniques, self-talk techniques and psychological support.